Chinese-style modernization - Munkhuu, Erdenebayar (Journal of International Studies, 2023)
Abstract: The policymakers in China consider that the way towards wealthy and powerful nation would be to achieve modernization in all aspects as many other developed countries did so. However, the modernization process in China has its own characteristics and, moving forward, it is intended to be developed into an internationally recognized model. Since there are a number of external and internal challenges may be encountered during the process including a proper reformation of the political system that could have a decisive impact on the successful modernization. The first part of this article will briefly explain what the modernization is and the theory of modernization, while the second part outlines the overall process of modernization in China and the main features and goals of "Chinese-Style Modernization". In the final part, the author shares his views on the possibilities of implementation and the challenges that may be faced. Хятад маягийн модернизац Хураангуй: БНХАУ-ын бодлого тодорхойлогчид тус улсын чинээлэг, хүчирхэг болох арга зам нь бусад өндөр хөгжсөн улсын нэгэн адил модернизацид бүх талаар хүрэх хэмээн үзэж байна. Гэхдээ тус улсын модернизацийн үйл явц өөрийн гэсэн онцлогтой байх бөгөөд цаашид олон улсад хүлээн зөвшөөрөгдсөн загвар болгон төлөвшүүлэхийг зорьж буй ажээ. Уг үйл явцад гадаад болон дотоод багагүй сорилт байгаагаас улс төрийн тогтолцоог хэрхэн шинэчлэхээс амжилттай хэрэгжих эсэх нь хамаарах магадлалтай юм. Энэхүү өгүүллийн эхний хэсэгт модернизац хэмээх ойлголт, онолын талаар товч тайлбарлаж, хоёрдугаар хэсэгт Хятадын модернизацийн ерөнхий үйл явц болон “хятад маягийн модернизац”-ийн голлох зорилт, онцлогийг авч үзэн, гуравдугаар хэсэгт хэрэгжих боломж, тулгарч болох сорилтын талаар санал бодлоо хуваалцлаа. Түлхүүр үгс: Модернизац, хятад маягийн модернизац, боломж, сорилт